Trayectorias tempranas en el inicio de la vida adulta en México - Pérez Baleón, Guadalupe Fabiola (El Colegio de México A.C., 2014)
The article examines the trajectories most common in the configuration of the adult life of three cohorts of Mexican men and women. It can be established a greater diversity of sequence in women given by the increase of their schooling and labor participation. Men were concentrated around two trajectories. The results confirmed the existence of gender regulations present between men and women but also among women and among men. This regulation is interconnected with socio-economic inequalities to produce trajectories that are more characteristic to certain social groups and determinate time and place.